Effectiveness and safety of teclistamab for relapsed or refractory multiple myeloma: a systematic review and meta-analysis - Li, Wenze; Zhao, Defeng; Jiao, Yu; Dong, Weilin; Wang, Ziyi; Yan, Xiaojing (Frontiers in Immunology, 2025)
BackgroundMultiple myeloma (MM) is a hematological malignancy with limited treatment options for patients with relapsed/refractory MM (RRMM). Teclistamab, a B-cell maturation antigen (BCMA) × CD3 bispecific antibody, has shown promising results in clinical trials and real-world studies.MethodsPubMed/MEDLINE, Web of Science, EMBASE, Cochrane Library, ClinicalTrials.gov, and meeting libraries were searched from inception to 14 November 2024. The assessed outcomes included overall survival (OS), progression-free survival, time to next treatment, duration of response, overall response rate (ORR), ≥complete response (≥CR), ≥very good partial response (≥VGPR), VGPR, partial response, and adverse events.ResultsIn total, 34 studies involving 4,064 patients were included. In pairwise meta-analysis, teclistamab demonstrated superior OS [hazard ratio (HR) = 0.69, 95% confidence interval (CI): 0.54–0.89; p = 0.037] compared to existing RRMM treatments. Real-world studies showed comparable ORR (62%, 95% CI: 58%–66%) but slightly lower survival outcomes, possibly because of shorter follow-up times and higher-risk populations. Subgroup analyses revealed enhanced efficacy with combination therapies (ORR: 85% vs 62%, p < 0.0001) and notable clinical benefits in the China cohort (≥VGPR: 77%, ≥CR: 58%). Safety profiles indicated manageable cytokine release syndrome and immune effector cell-associated neurotoxicity syndrome, though infection risks required vigilant management.ConclusionsTeclistamab continues to be a promising and effective treatment option for RRMM patients, including those previously exposed to BCMA-targeted therapies, and offers new hope for overcoming resistance and achieving better early disease control. Further research is needed to optimize its application in diverse populations, particularly in Asian cohorts.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/#myprospero, identifier CRD42025633838.